Exploring the Factors Considered by People Living with HIV and Their Partners during Preconception. (May 2017) - Kennedy, V. Logan; Collins, Micaela; Yudin, Mark H.; Serghides, Lena; Walmsley, Sharon; Angel, Jonathan B.; Ongoiba, Fanta; Powis, Jeff; Smaill, Fiona; Tharao, Wangari; Rachlis, Anita; Silverman, Michael; et al.
Data are lacking on factors that may impact conception-related decision-making among individuals living with HIV. This study's aim was to shed light on these considerations. Participants were invited to complete a survey on preconception considerations. A rank-ordered logit model was fit to estimate the relative importance of listed consideration factors; the interaction of HIV status and the factors was assessed. Fifty-nine participants living with HIV and 18 partners (11 HIV-negative participants and 7 living with HIV) were included. Risk of vertical and horizontal HIV transmission and the effect of antiretroviral therapy on the fetus were the top considerations. However, individuals living with HIV prioritized vertical transmission, whereas HIV-negative participants prioritized horizontal transmission. Other factors of importance were probability of conception, stress of trying to conceive, cost associated with fertility clinics, and stigma associated with certain conception methods. This study builds our understanding of the preconception considerations for people living with HIV.